Detection of Endothelial Dysfunction Using Skin Temperature Oscillations Analysis During Local Heating in Patients With Peripheral Arterial Disease. (August 2016) - Parshakov, Aleksey; Zubareva, Nadezhda; Podtaev, Sergey; Frick, Peter
Abstract: Objective: The purpose of this study was to examine correlations between laboratory markers of ED and the degree of endothelium‐dependent vasodilation using WAST during a local heating test in patients with PAD. Materials and methods: The study population consisted of 17 healthy subjects and 38 patients with PAD. The ST on the plantar surface of the first toe was measured during the test, and the inverse wavelet transform was applied to reconstruct the ST signals in three frequency bands corresponding to myogenic, neurogenic, and endothelial mechanisms of vascular tone regulation. Results: In healthy subjects, a local increase in temperature of up to 42°C caused a greater than threefold increase in the amplitudes of foot ST oscillations. Among patients with PAD, the response to the test was much weaker in all frequency ranges. The level of vasodilation dysfunction correlated with the level of artery stenosis in the lower extremities and with laboratory markers of ED (endothelin, homocysteine, and von Willebrand factor). Conclusion: WAST can be considered as a low cost, portable, and easy to use technique for the noninvasive assessment of ED.